Fintech, sustainability, and risk: A bibliometric exploration of global trends in digital lending post-covid-19 - Suhardi, Suhardi (International Journal of Applied Finance and Business Studies, 2025)
This study examines the transformation of digital lending in the post-COVID-19 era using a bibliometric approach, using the LinLog method, analyzing 1,250 indexed documents in Scopus on the Emerald website (2020–2025). VOSviewer and Bibliometrix tools were employed to identify thematic trends, conceptual networks, and research density. The overlay and density visualizations highlight the dominance of themes such as financial inclusion, digital finance, and strategy, with recent research focusing on sustainability, technology adoption, and risk management. Geographically, the Global South remains underrepresented in the literature. Three major challenges emerged: (1) systemic risks such as money laundering and cybersecurity vulnerabilities, (2) gender gaps in digital service access, and (3) fragmented ESG regulation. Visualization results also revealed growing interest in emerging topics like blockchain and AI ethics, though still underexplored. The study proposes adaptive regulatory sandboxes, gender-responsive financial literacy programs, and harmonising global standards as strategic policy responses. Future research should examine the long-term impact of digital lending on economic inequality and the role of technologies in enhancing transparency. These findings contribute to academic and practical discussions on building a resilient, inclusive, and SDG-aligned digital lending ecosystem.